2020
DOI: 10.1002/ldr.3751
|View full text |Cite
|
Sign up to set email alerts
|

The long‐term effects of underground mining on the growth of tree, shrub, and herb communities in arid and semiarid areas in China

Abstract: Underground mining (as opposed to open‐cast) often causes large‐scale subsidence, leading to various types of disturbances to surface vegetation. Adequate quantitative assessment of the long‐term effects of underground mining on the growth of different plant communities is important and still lacking. To address these issues, a vegetation growth contract model (VGCM) was proposed, and six indicators including the growth trend (GT), annual growth (AG), normalized spectrum entropy (Hsn), as well as the average v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…In the Yugang mining area, six kinds of normalized difference vegetation index (NDVI) based indicators were proposed to represent the changes in the plant communities under the long-term effects of underground mining. Average decreases of 15.10%, 6.79%, and 4.03% in these indicators were reported for the herb, tree, and shrub communities, respectively (Mi et al, 2021). These studies revealed that the effects of mining-induced ground deformation on plants could be comprehensive, and there could be great differences in the responses of various plant communities to ground deformation on a long time scale.…”
Section: Introductionmentioning
confidence: 79%
“…In the Yugang mining area, six kinds of normalized difference vegetation index (NDVI) based indicators were proposed to represent the changes in the plant communities under the long-term effects of underground mining. Average decreases of 15.10%, 6.79%, and 4.03% in these indicators were reported for the herb, tree, and shrub communities, respectively (Mi et al, 2021). These studies revealed that the effects of mining-induced ground deformation on plants could be comprehensive, and there could be great differences in the responses of various plant communities to ground deformation on a long time scale.…”
Section: Introductionmentioning
confidence: 79%
“…This may be the heightened sensitivity of the NDVI to seasonal variations, rainfall, vegetation phenology, and other environmental factors that impact biodiversity (Madonsela et al, 2018; Pau et al, 2012). Consequently, using vegetation cover or the NDVI as the primary criterion for evaluating restoration effectiveness may require further evaluation regarding validity as a tool for regulatory monitoring standards (Han et al, 2021; Hoffmann, 2022; Madonsela et al, 2018; Mi et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…One of the most important ecological and environmental issues that western China mining areas are facing is vegetation deterioration ( Liu et al., 2021a ). The damage to surface vegetation caused by coal mining subsidence in semi-arid mining areas is currently the subject of extensive research ( Mi et al., 2021 ). Researchers have found useful monitoring techniques as well as principles governing the temporal and spatial patterns of surface vegetation disturbance in such subsidence areas ( Bian et al., 2020 ; Liu et al., 2020 ; Liu et al., 2021a ).…”
Section: Introductionmentioning
confidence: 99%